Patterns of farm financial structure : a cross-section view of economic and physical determinants - Horton, Donald Clare (Princeton : Princeton University Press, 1957)
The book is centered on the relationship between economic and financial characteristics of agriculture. It gives data on indicators of economic characteristics, farm and asses size composition.
"A study by the National Bureau of Economic Research, New York."
includes index.
sju 25/01/2019
Loans
Keywords: Agricultural credit; Agriculture